Mentoring for wellbeing across the professions and disciplines - Kutsyuruba, Benjamin; Walker, Keith D. (Perspectives in mentoring., 2025)
Mentoring for Wellbeing Across the Professions and Disciplines offers invaluable insights into how mentorship can enhance wellbeing across various fields and professional settings. By focusing on the dual aims of personal support and professional learning, this book highlights the often-overlooked positive impact of mentoring on both mentors and mentees. The authors provide practical advice and theoretical perspectives on how developmental relationships foster mutual trust and benefit all parties involved, ultimately helping mentees flourish in their roles and develop essential skills. The book delves into the connection between mentorship and wellbeing and explores how mentoring can promote mental health, build resilience, and sustain emotional, psychological, and social wellbeing in different organizational settings. Through the collection of chapters from international authors, the book examines the theory and practice of mentorship, offering a comprehensive understanding of how mentoring can enhance wellbeing in K-12 schools, higher education, business, healthcare, pastoral care, and even aviation. The chapter authors present stories and perspectives that deepen our understanding of the multifaceted benefits of mentoring. By addressing various dimensions of wellbeing--physical, social, emotional, financial, intellectual, spiritual, environmental, cultural, and occupational--this volume provides a holistic view of the positive impact of mentoring. It discusses developmental relationships, program initiatives, and strategies that foster positive organizational cultures and personal growth. Mentoring for Wellbeing Across the Professions and Disciplines is a must-read for anyone interested in the transformative power of mentoring, offering practical applications and new avenues for future research and study.